Progress in international geopolitical research from 1996 to 2015 - Song, Tao; Lu, Dadao; Liang, Yi; Wang, Qian; Lin, Jing (Journal of geographical sciences, 2017)
Focusing on international relations from the perspective of geography, geopolitics exerts powerful influences on the course of economic and political development in the world. In the tide of globalization and information technology, geopolitics has become an important subject for global pattern interpretation and policy making. It is essentially important to have a scientific and systematic review on international geopolitics to promote its development. Based on the bibliometric statistics, the paper reviews the research development of geopoli- tics on the Web of Science from 1996 to 2015. The history, journals, papers and key research areas of geopolitics have been revealed in the paper. By the analysis of bibliometric statistics, the number of papers recently published in the journals of political geography and related geography journals continues to increase. The key areas of geopolitical papers which are globally highly cited include geopolitical interpretation of the countries and borders, critical geopolitics, emotional geopolitics, feminist geopolitics and other topics. Before the year of 2000, the state and borders were hot topics of the geopolitical research. Yet since 2000, it has been the trend that the geopolitics is increasingly set in the context of geographical implica- tions. At the same time, critical geopolitics appears to be the main area of geopolitical re- search, especially transitioning from traditional geopolitics towards the humanism-em- beddedness （such as emotional geopolitics, feminist geopolitics）. The paper then systemati- cally reviews the branch trends of geopolitical research, including the borders and the territory global geo-culture and geo-economics, Chinese models of geopolitics, resource conflicts and ecological politics, as well as emotional geopolitics. Finally, it puts forward the implication that Chinese geopolitical studies should reinforce the importance of geographical space and scale use the process of description and multiple methods, as well as integrate humanistic thoughts in order to further enrich the theories and practices of geopolitical research.